Is Our Nation Fully Prepared to Provide Disaster Relief to Victims Needing Dental Care? - M. Elaine Neenan, MS, DDS, MPH (Blackwell Synergy, 2005)
When Hurricane Katrina devastated New Orleans and other communities along the Gulf Coast, the evacuation displaced hundreds of thousands of people, distributing them throughout 48 states without medical charts or prescription medications, extending the impact beyond the strike zone.